Increasing Student Creativity through Memory Photo Box Product Innovation as a Personal Gift Based on Emotional Values: Peningkatan Kreativitas Mahasiswa melalui Inovasi Produk Memory Photo Box sebagai Hadiah Personal Berbasis Nilai Emosional - Ria Rosanti; Anggit Dyah Kusumastuti (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
This activity aims to enhance student creativity through the development of the Memory Photo Box as an innovative product with high emotional value that can serve as a personalized gift. This product was chosen for its ability to combine aesthetic elements, functionality, and emotional appeal, which increase both its attractiveness and market value. The implementation methods included hands-on training, creative idea brainstorming, and group discussions to design and create the Memory Photo Box. Evaluation was conducted using a pretest-posttest approach to assess improvements in students’ creativity, understanding of emotional value in products, and the overall quality of their final creations. The results indicated a significant improvement across all three aspects. The outcomes of this activity include the physical Memory Photo Box products, an activity report, a scientific article, and the emergence of entrepreneurship potential based on student creativity. This activity is expected to serve as a real-life implementation of the Creativity and Innovation course, providing not only theoretical knowledge but also practical experience that directly contributes to the development of students’ soft skills.